PGH1, the precursor for the anti-inflammatory prostaglandins of the 1-series, is a potent activator of the pro-inflammatory receptor CRTH2/DP2. - Schröder, R; Xue, L; Konya, V; Martini, L; Kampitsch, N; Whistler, J; Ulven, T; Heinemann, A; Pettipher, R; Kostenis, E (2012)
Prostaglandin H(1) (PGH(1)) is the cyclo-oxygenase metabolite of dihomo-γ-linolenic acid (DGLA) and the precursor for the 1-series of prostaglandins which are often viewed as "anti-inflammatory". Herein we present evidence that PGH(1) is a potent activator of the pro-inflammatory PGD(2) receptor CRTH2, an attractive therapeutic target to treat allergic diseases such as asthma and atopic dermatitis. Non-invasive, real time dynamic mass redistribution analysis of living human CRTH2 transfectants and Ca(2+) flux studies reveal that PGH(1) activates CRTH2 as PGH(2), PGD(2) or PGD(1) do. The PGH(1) precursor DGLA and the other PGH(1) metabolites did not display such effect. PGH(1) specifically internalizes CRTH2 in stable CRTH2 transfectants as assessed by antibody feeding assays. Physiological relevance of CRTH2 ligation by PGH(1) is demonstrated in several primary human hematopoietic lineages, which endogenously express CRTH2: PGH(1) mediates migration of and Ca(2+) flux in Th2 lymphocytes, shape change of eosinophils, and their adhesion to human pulmonary microvascular endothelial cells under physiological flow conditions. All these effects are abrogated in the presence of the CRTH2 specific antagonist TM30089. Together, our results identify PGH(1) as an important lipid intermediate and novel CRTH2 agonist which may trigger CRTH2 activation in vivo in the absence of functional prostaglandin D synthase.